Penggunaan Metode Peer Teaching pada Peningkatan Hasil Belajar IPS SD di Yogyakarta - Caecilia Titin Nilawati; Sukadari Sukadari (UM Purwokerto Press, 2022)
Peer teaching is a learning model that allows students to share their knowledge with their peers or teach their peers. This is done because the social studies learning outcomes of fourth grade students at SDN Nglanggeran are still relatively low. In addition, the learning carried out by the teacher has not been innovative and monotonous. This learning method is student-centered. The purpose of this study was to improve social studies learning outcomes regarding ethnic and cultural diversity through peer teaching methods for fourth grade students at SDN Nglanggeran. This research uses classroom action research method. The research subjects were the fourth grade students of SDN Nglanggeran Patuk, totaling 22 students, consisting of 8 boys and 14 girls. Data were collected by using a learning outcomes test technique with 10 multiple choice questions. The results showed an increase in student learning outcomes which can be seen from the increase in the average score from 72.2 (pre-cycle) to 76.6 (cycle I), increasing to 81.5 (cycle II). Therefore, it can be said that the use of this peer teaching method can improve social studies learning outcomes for students so that teachers are expected to use the peer teaching method.